Population Genetics of Long-Tongued nectar bat, macroglossus minimus (chiroptea pteropodidae) in Malaysian Borneo - Zaniah, Ishak (Universiti Malaysia Sarawak, UNIMAS, 2013)
The long-tongued nectar bat, Macroglossus minimus is the smallest of the family Pteropodidae commonly found both in primary and secondary tropical moist forest. M. minimus is chosen as a model for this study because of lack information on their genetic relationship within the species itself. The main objective of this study is to determine the genetics structure of M. minimus from different populations in Malaysian Borneo using partial primer of cytochrome b (cyt b) mitochondrial gene. This population is hypothesised to show genetic variation due to the isolation by geographical distance. The result showed that there are no genetic variations among M. minimus populations in Sarawak. However, there are genetic divergence between populations of Sabah and southern part of Sarawak. The variation of genetic structure might be related to historical event. More samples should be included in future studies to confirm the genetic divergence of the species within and among their populations.